2010
DOI: 10.1002/qre.1162
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical model of the occurrence of human error in manufacturing processes

Abstract: Various types of phenomena contribute to the variability of process results. Their common feature is randomness. Some of them can be described by continuous probability distributions, for example, the performance of machines or the properties of processed material. There are also discretely distributed contributions, such as human errors or machine failures. Six sigma methodology encompasses both continuous and discrete phenomena by expressing measures of variability by the so-called 'sigma measure'. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 3 publications
0
26
0
1
Order By: Relevance
“…También sobresalen otros estudios en la industria de la manufactura con enfoque de Confiabilidad (Torres, Nadeau y Landau, 2019;Muxfeldt y Steil, 2018;Refflinghaus y Kern, 2018;Salas-Arias et al, 2018;Lopes y Forster, 2013;Power y Fox, 2014;Ruiz-Moreno y Trujillo, 2012;Brito et al, 2011;Myszewski, 2010;Paun et al, 2011;Boring, Griffith y Joe, 2007;Taylor-Adams y Kirwan, 1997;Baber y Stanton, 1996;Razak, Kamaruddin y Azid, 2008;Ruckart y Burgess, 2007;Drury, 2002;Drury y Watson, 1999;Fujita y Hollnagel 2004) y, la industria militar (Yu et al, 2000Wang y Zhao, 2010).…”
Section: Resultsunclassified
“…También sobresalen otros estudios en la industria de la manufactura con enfoque de Confiabilidad (Torres, Nadeau y Landau, 2019;Muxfeldt y Steil, 2018;Refflinghaus y Kern, 2018;Salas-Arias et al, 2018;Lopes y Forster, 2013;Power y Fox, 2014;Ruiz-Moreno y Trujillo, 2012;Brito et al, 2011;Myszewski, 2010;Paun et al, 2011;Boring, Griffith y Joe, 2007;Taylor-Adams y Kirwan, 1997;Baber y Stanton, 1996;Razak, Kamaruddin y Azid, 2008;Ruckart y Burgess, 2007;Drury, 2002;Drury y Watson, 1999;Fujita y Hollnagel 2004) y, la industria militar (Yu et al, 2000Wang y Zhao, 2010).…”
Section: Resultsunclassified
“…However, the available research does not provide a model of HEP as a time-based function of the risk factors. HEP models by Givi et al (2015) and Myszewski (2010) show HEP as a continuous function of time but do not account for workload in their models. Some of the existing fatigue models (Dode, Greig, Zolfaghari, & Neumann, 2016;Perez et al, 2014) show fatigue as a function of time and workload (% maximum voluntary contractions); however, there are few studies that provide a quantitative model directly linking workload to HEP.…”
Section: Future Workmentioning
confidence: 99%
“…It has been shown that the error rate of a worker decreases as he/she accumulates more experience and it increases by fatigue (Giuntini, 2000;Myszewski, 2010). The aim of Phase 3 of the thesis is to model the error rate of a worker taking into account the PSFs of learning and physical fatigue and their opposites, forgetting and recovery.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of Phase 3 of the thesis is to model the error rate of a worker taking into account the PSFs of learning and physical fatigue and their opposites, forgetting and recovery. The error rate of a worker, on one hand, decreases as he/she accumulates more experience due to repetition in accordance with his/her learning curve (Giuntini, 2000), but at the same time, he/she accumulates fatigue, which increases the error rate (Myszewski, 2010;Michalos et al, 2013). Rest breaks, alleviate worker fatigue (Krajcarski & Wells, 2008) and decrease the probability of committing mistakes/errors on a job, but at the same time, they cause forgetting (Anzanello & Fogliatto, 2011;Froehle & White, 2013), which is an error-increasing PSF (ElMaraghy et al, 2008).…”
Section: Introductionmentioning
confidence: 99%